Enantioseparation of racemic trans-δ-viniferin using high speed counter-current chromatography based on induced circular dichroism technology - Han, Chao; Xu, Jinfang; Wang, Xiaobing; Xu, Xiaoming; Luo, Jianguang; Kong, Lingyi (Journal of Chromatography A, 2014)
•A new method for chiral separation of TVN racemate using HSCCC was established.•Induced circular dichroism was first applied to optimize the chiral HSCCC conditions.•This method could be applied to improve the production rate of the chiral separation. A preparative chiral high speed counter-current chromatography (HSCCC) method based on induced circular dichroism (ICD) spectrum was developed to separate trans-δ-viniferin (TVN) enantiomers successfully. The important parameters for the chiral HSCCC separation process, including the type of chiral selector (CS), the concentration of chiral selector and the equilibrium temperature, were optimized using induced circular dichroism spectrum. The final separation procedure was established with a biphasic solvent system composed of n-hexane–ethyl acetate–25mmolL−1 hydroxypropyl-β-cyclodextrin aqueous solution (5:5:10, v/v/v) in the head-to-tail elution mode at 5°C. Under optimum chiral HSCCC separation conditions, 8.2mg of (7S, 8S)-TVN (1) and 9.4mg of (7R, 8R)-TVN (2) were successfully separated from 20mg TVN enantiomers with the purity of 99.51% and 99.36%, respectively.